Efforts to Increase Students' Knowledge through Education about Dengue Fever: Upaya Peningkatan Pengetahuan Siswa Melalui Edukasi Tentang Penyakit Demam Berdarah Dengue - La Ode Alifariki; Adius Kusnan (Yayasan Ahmar Cendekia Indonesia, 2022)
Dengue hemorrhagic fever (DHF) is also known as Dengue Hemorrhagic Fever (DHF), dengue fever (DF), dengue fever (DD), and Dengue Shock Syndrome (DSS). This disease can affect all ages, both children and adults. This community service was carried out with the aim of educating students about the importance of preventing DHF in the school environment. This counseling was carried out by a service team consisting of the Faculty of Medicine, Halu Oleo University along with students with an audience of 30 students from SMPN 20 Kendari. The results of measuring students' knowledge showed that there were differences in knowledge about DHF before and after counseling. Abstrak Demam berdarah dengue (DBD) dise-but juga Dengue Hemorrhagic Fever (DHF), dengue fever (DF), demam dengue (DD), dan Dengue Shock Syndrome (DSS). Penyakit ini dapat menyerang semua umur baik anak-anak maupun orang dewasa. PkM ini dilaksanakan bertujuan untuk mengedukasi siswa tentang pentingnya pencegahan DBD di lingkungan sekolah. Penyuluhan ini dilakukan oleh tim pengabdi yang terdiri atas Fakultas Kedokteran Universitas Halu Oleo bersama mahasiswa dengan khalayak adalah siswa SMPN 20 Kendari sebanyak 30 orang. Hasil penguuran pengetahuan siswa menunjukkan bahwa ada perbedaan pengetahuan tentang DBD sebelum dan sesudah penyuluhan.